Implementation of the Scaffolding Method in Improving Learning Outcomes with the Material of Respecting and Appreciating the Beliefs of Others at SD Negeri 095253 Talun Madear - Sriyani; Purba, Jamaluddin; Muliati; Lubis, Nining Indah Lestari (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2025)
This study aims to analyze the implementation of the scaffolding method in improving learning outcomes on the material "Respecting and Appreciating Other People's Beliefs in the School Environment" at SD Negeri 095253 Talun Madear. The scaffolding method is a learning strategy that provides gradual guidance to students until they are able to achieve understanding and independence in learning. This approach is considered effective in building an attitude of tolerance and improving students' understanding of the importance of mutual respect in social life at school. This study uses a quantitative method with a classroom action research (CAR) design. Data were obtained through observation, learning outcome tests, and interviews with students and teachers. The results showed that the gradual implementation of the scaffolding method was able to improve students' understanding of the material being taught. This can be seen from the increase in students' average scores in each learning cycle, as well as a change in attitudes that are more positive in appreciating differences in beliefs in the school environment. In addition, students become more active in discussions and more confident in expressing their opinions regarding the values ​​of tolerance. Thus, it can be concluded that the scaffolding method is an effective strategy in improving student learning outcomes, especially in learning that emphasizes social aspects and values ​​of togetherness. The application of this method is recommended for teachers to create a more interactive and meaningful learning atmosphere for students